ИРГЭДИЙН УЛС ТӨРИЙН ОРОЛЦОО БА ТҮҮНД НӨЛӨӨЛЖ БУЙ УЛС ТӨРИЙН ХҮЧИН ЗҮЙЛС - У.Батцэрэн (Politology, 2023)
Mongolians is a nation with a long traditions history of statehood. The present democratic system of political life cannot manifest the nature of democracy without the civic participation. Citizens’ political engagement is a process that affects organizations, policies, decisions and activities. The basis of democracy is the participation of citizens. As democracy and political decision-making have emerged, citizen perceptions of democracy can be further strengthened. a legal basis for political participation in Mongolia has established in the Constitution and other legislative and political documents. However, in practice the political participation of citizens the people is low. The main reason for this is that political, legal, social and economic conceptual framework is not yet sufficiently developed. Therefore, the development of political participation of citizens in democratic societies has emerged as an acute necessity. In Mongolia, political participation of citizens is very important. The category of political participation of citizens was almost unknown in our political science until 1990’s. From the beginning of the 20th century, when has been Bogdo-khan’s governance and during almost all twentieth century when the communist regime has governed in the society the people was used to worship and therefore, citizens’ voluntary involvement in civil affairs was almost impossible.Therefore, Department of Political Studies of Institute of Philosophy ( Mongolian Academy of Sciences) has conducted a comprehensive expert survey on "Representative Democracy and Political Participation in Mongolia". The article is based on the findings of this study.